Castes and polymorphisms in Neotropical Social Wasps - da Silva, Marjorie [UNESP]; Mateus, Sidnei; Noll, Fernando Barbosa [UNESP] (Springer Nature, 2020)
Neotropical social wasps have a set of chimeric characteristics that make them unique and difficult to fit into current theories on the evolution of social behavior (Noll and Wenzel, Biol J Linn Soc 93: 509-22, 2008). Among them, the presence of more than one functional queen (polygyny), absence of strong morphological differentiation, and flexibility between casts result in relaxation of ovarian control and breeding opportunity for workers (West-Eberhard, Science 200: 441-3, 1978; Noll, Sociobiology 60: 347-54, 2013). Adding to these particularities, the Polistinae wasps, especially those belonging to the Epiponini, reached a great radiation and evolutionary success in the Neotropical region due to the unique mode of social organization: colony foundation by a swarm (Jeanne, The swarm-founding Polistinae. In: Ross KG, Matthews RW (eds) The social biology of wasps. Cornell University Press, Ithaca, pp 191-231, 1991), where several or many reproductive females (queens) tolerate each other laying eggs. This chapter deals in general with aspects of the complex caste delimitation, the division of labor in the colony, the recruitment and foraging, and the lack of colony in social wasps, with emphasis on swarm founders.
Keywords: Defense; Foraging; Polistinae; Polygyny; Syndromes